Acute Neurological Presentation in Children With SARS-CoV-2 Infection - Riva, Antonella; Piccolo, Gianluca; Balletti, Federica; Binelli, Maria; Brolatti, Noemi; Verrotti, Alberto; Amadori, Elisabetta; Spalice, Alberto; Giacomini, Thea; Mancardi, Maria Margherita; Iannetti, Paola; Vari, Maria Stella; et al. (Frontiers in Pediatrics, 2022)
Background: In the pediatric population, the knowledge of the acute presentation of SARS-CoV-2 infection is mainly limited to small series and case reports, particularly when dealing with neurological symptoms. We describe a large cohort of children with acute SARS-CoV-2 infection, focusing on the neurological manifestations and investigating correlations between disease severity and population demographics. Methods: Patients aged 0-18 years with a positive molecular swab were recruited between April 2020 and March 2021 from a tertiary Italian pediatric Centre. Clinical data, imaging, and laboratory tests results were retrieved from our local dataset and statistically analyzed. Results: 237 patients with a median age of 3.2 years were eligible; thirty-two (13.5%) presented with neurological symptoms including headache (65.6%), altered awareness (18.8%), ageusia/anosmia (12.5%), seizures (6.3%), and vertigo (6.3%), combined in 7 (21.9%) cases. Respiratory (59.5%) and gastrointestinal (25.3%) symptoms were the most common among the 205 (86.5%) patients without neurological involvement. Neurological symptoms did not significantly influence the severity of the triage access codes. Moreover, pre-existing medical conditions were not higher in the group with neurological manifestations. Overall, fifty-nine patients (25%, 14/59 with neurological symptoms) required treatment, being antibiotics, systemic steroids, and heparin those most prescribed. Conclusions: Our study supports the overall benign course of the SARS-CoV-2 infection in children. Neurological manifestations, except for headache, remain a rare presenting symptom and disease severity seems unrelated to pre-existing medical conditions.